Gambaran Pengetahuan Wanita Usia Subur Tentang Manfaat IVA Test - Fardila Elba; Imma Kristy Nathalia (stikes dharma husada bandung, 2018)
The incidence of cervical cancer in Indonesia is quite high at 25.91%. Cervical cancer can be detected early with VIA test. VIA test is one of the first steps to detect abnormalities in the cervix. VIA test is an easy check, cheap, and can be done by the midwife. However, the coverage of VIA test in Indonesia is still low about 2.45% of the target coverage determined by the government that is 80%. The low coverage of VIA test screening in Indonesia is influenced by the low knowledge of women. Women's low knowledge will influence their participation in screening. This research uses cross-sectional method approach. The sample in this study is Women of Childbearing Age aged 15-49 years in the working area of Puskesmas Soreang. Sampling uses proportional stratified random sampling technique with a sample size of 76 respondents. Data analysis uses Fisher Exact Test. The results show that there is a significant relationship between knowledge and attitude of WUS with p value = 0.000 (p > 0.005). Based on the results of this study, it can be concluded that there is a relationship between knowledge and attitude of WUS on VIA test for early detection of cervical cancer.